Al-Qur’an Sebagai Sumber Ajaran Islam Pertama - Saryadi (ALBAHRU, 2022)
The Qur'an is the main source of Islamic teachings and the guiding principle of life for every Muslim. The Qur'an not only contains instructions about the relationship between humans and God, but also regulates human relations with each other, as well as humans with the natural surroundings. To understand the teachings of Islam perfectly, it is necessary to understand the content of the Qur'an and practice it in daily life seriously and consistently. As is known, the Qur'an was revealed in Arabic, both in pronunciation and in uslub. A language rich in vocabulary and meaning. Therefore, it is very important for us to study the study of the Qur'an, so that we can examine more deeply about the verses of the Qur'an as a source of Islamic teachings, both in terms of language, purpose, use, purpose, content that can be used. we apply in life. This article "Al-Qur'an as the First Source of Islamic Teachings" may be a reminder for us as the people of the Prophet Muhammad in making the Qur'an as a guide and guide for life. The method used in this study is literature research. The results of this study conclude that the Qur'an as a source of Islamic teachings is very important for us to study and learn because the Qur'an is a guide in all our life activities and brings our happiness in this world and the hereafter.